2020
DOI: 10.1103/physreve.101.032118
|View full text |Cite
|
Sign up to set email alerts
|

Cloaking the underlying long-range order of randomly perturbed lattices

Abstract: Random, uncorrelated displacements of particles on a lattice preserve the hyperuniformity of the original lattice, that is, normalized density fluctuations vanish in the limit of infinite wavelengths. In addition to a diffuse contribution, the scattering intensity from the the resulting point pattern typically inherits the Bragg peaks (long-range order) of the original lattice. Here we demonstrate how these Bragg peaks can be hidden in the effective diffraction pattern of independent and identically distribute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 58 publications
3
48
0
Order By: Relevance
“…In addition, we note that in this work we discovered a hyperuniformity-preserving operation in two dimensions: SW transformation. Previously, it was found that operations such as "uncorrelated" stochastic displacements in perfect lattices preserve hyperuniformity but could change the hyperuniformity class of the systems (40,42,43), similar to what we observed in this work. Moreover, hyperuniformity-generating operations that can convert nonhyperuniform point patterns into hyperuniform materials have also been discovered (28,69).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…In addition, we note that in this work we discovered a hyperuniformity-preserving operation in two dimensions: SW transformation. Previously, it was found that operations such as "uncorrelated" stochastic displacements in perfect lattices preserve hyperuniformity but could change the hyperuniformity class of the systems (40,42,43), similar to what we observed in this work. Moreover, hyperuniformity-generating operations that can convert nonhyperuniform point patterns into hyperuniform materials have also been discovered (28,69).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Further work in this direction is certainly needed. Future investigations may also consider the possibility of artificially tuning the Gaussian behavior through local particle displacements [34].…”
Section: Hidden Order Beyond Hyperuniformity In Critical Absorbing Statesmentioning
confidence: 99%
“…1(d)]. Ordered lattices provide a strong decay for small wave vectors and an oscillating σ 2 (R) with a dip each time R is somewhat smaller than integer multiples of the average interparticle distance [35].…”
Section: Methodsmentioning
confidence: 99%